Analysis of electron behaviour around a spring-shape filament inside a low-energy electron gun. Issue 1 (1st April 2022) - Matsumoto, Y; Nakano, H; Kisaki, M; Shinto, K; Sasao, M; Wada, M
Abstract: Electron behaviour inside a low-energy electron gun based on a spring-shape filament were studied with experiment and Particle-In-Cell simulation. The energy range of the electron beam which we expected was from 1 to 20 eV. The analysis told that smaller size of filament is more useful to improve electron density in front of an extraction hole in the gun to enhance beam current. Relation between a space potential distribution in the gun and electron transport was also studied. A heater voltage to drive a filament for thermionic electron emissions has another role to form a spatial potential distribution in the gun. The potential guides electrons, which are at a distant area from the beam extraction hole, toward the hole. It can be a significant help to realize efficient electron extraction by a beam extraction electric field induced near the hole.